FEATURES OF FORMING OF THE PHOTOSYNTHETIC PRODUCTIVITY OF PLANTS OF SORTS OF KIDNEY BEAN ARE DEPENDING ON DEPTH OF SEEDING - Овчарук, В. І.; Овчарук, О. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The article reviews the researches results of the highly productive varieties of common beans, the photosynthetic formation productivity in the conditions of the Right-Bank Forest-Steppe. By the results ofthe researches established dependence of the photosynthetic productivity from the varietal characteristics of kidney beans and the seeding depth.The highest indicators of the assimilatory surface was formed by the crops of Bukovynka variety at the sowing depth of 4-5 sm and were 40,3 thousands m2/ha during the phase of flowering-seed formation.With the different depth the indicators of the leaf surface area were decreased by 1,0-1,1 thousands m2/ha. These indicators were the lowest in Schedra variety at the sowing depth of 2-3 sm. It was established that the most effectively leaf surface area of crops have worked during theflowering period of kidney bean plants. In particular, the most elevated figures of the photosynthetic potential in the research were found in Bukovynka variety at the sowing depth of 4-5 sm, which were 0,751mln m2 × day/ha. These figures were the lowest in Perlyna variety – 0,659 mln m2 × day/ha. The largest increase of dry matter in kidney beans crops were found during the period from the flowering phase to the pod-filling phase. The highest number of dry matter (6,31 t/ha) on average for the period of studies was found in crops of Bukovynka variety at the sowing depth of 4-5 sm. As a result of calculations was established that the highest increase of pure productivity of photosynthesis in the research was during the period “first trigeminal leaf-beginning of flowering” of kidney bean plants. Namely the researched crops during the mentioned period have yielded from 5.12 to 5.47 g/m2 of dry matter per day at the sowing depth of 4-5 sm. At the sowing depth of 2-3 cm and 6-7 cm they’ve yielded from 5,09 to 5,43 g/m2 of dry matter per day.It was shared factors of influence during the formation of pure productivity shows that among studied factors the most impact on the change of an indicator has the genetic characteristics of a variety(factor A – 64%). Slightly lower influence has the seeding depth (factor B – 24%). The interaction of studied factors was at the level of 11%.